SEJARAH DAKWAH PADA MASA BANI UMAYYAH - Hatmansyah, Hatmansyah (UIN Antasari Banjarmasin, 2018)
The Umayyah dynasty became a major force in the development of propaganda spread throughout the world as well as being one of the first centers of political, cultural and scientific studies in the world since the Middle Ages. At the height of its greatness, its success in expanding Islamic power was far greater than that of the Roman empire. The history of Islamic preaching in the Umayyah Dynasty can be divided into two periods in the dynasty era in Damascus and in Cordoba. Islamic dawah at this time was carried out in three stages, first the expansion of the dawah area, the second was the development of science and the third was economic thought.